Evaluación del índice de sostenibilidad de las cuatro subzonas hidrográficas del departamento del Atlántico durante el periodo comprendido entre 2000 – 2020 (2025)
Environmental problems linked mainly to the development of different economic sectors have generated impacts on the water sustainability of large areas of territory worldwide. This situation has not been foreign to Colombia and the department of Atlántico, which have been significantly affected by the effects linked to climate change and poor planning in terms of sustainable development policies, generating direct impacts on the levels and flows of the basins, high rates of erosion, loss of biodiversity and low productivity of the land, which leads to impacts on the socio-environmental development of the communities in the territories and directly affects food security in the area. Likewise, the lack of clear public policies, focused mainly on the rational and efficient use of available natural resources, has caused wear and tear on these, which directly affects their availability and regeneration to meet future needs in terms of natural resources and the environment